Teacher Training In Colombia From A Historical Perspective - Jiménez, Aránzazu Bernardo; Betancourt, Blanca Lucia Cely (Migration Letters, 2024)
The objective of this article is to make a historical review of teacher training in Colombia with respect to the development of its competence, taking the period between the sixteenth century, when the first attempts at teacher training were made, and the major educational reforms of the twenty-first century, which have greatly influenced the formation of the profile of the foreign language educator. Finally, a historical review is made on the teaching of foreign languages in the educational processes of the country, influenced by social and political phenomena throughout history. As a methodology, the sources were selected and organized chronologically and a division of three major periods framed by the events of the country’s history and the milestones of the teaching profession was established.